دور فريق الهندسة المتزامنة في تحسين جودة المنتجات - داود غسان قاسم; نوري حيدر شاكر (Journal of Economics and Administrative Sciences, 2008)
Concurrent Engineering approved that it is distinguished technology efficiency as it reflect its affection on international great companies . Its becomes vital field connected with its ability to develop the products directly, as well as, its concentration on all local and international competition which need to research and expanded This study deals with (concurrent engineering) subject in (Dyala State Company for Electrical Industry) , to bring the benefits of this technology to develop the company goods by using of questionnaire as method to data collection for Sample of employees including high administrations managers and department management in the company to reach of outcomes to reinforce roles of concurrent engineering to products quality.